Integration of Indonesian Stock Market With Stock Market of The Highest Economic Countries - Saputra, Sahdan; Hendri, Wira (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
This study aims to analyze the integration between the Indonesian stock market and the stock markets of the world's leading economies, including the United States, China, Japan, Germany, France, India, and Brazil. The approach employed is a quantitative one, using weekly data from 2016 to 2023, with a total of 418 observations. The analytical methods utilized are Johansen and Juselius co-integration to examine long-term integration and pair-wise Granger causality to assess short-term integration. The findings reveal no long-term integration between the Indonesian stock market and the stock markets of the world's leading economies. However, in the short term, the Indian stock market shows some degree of integration with the Indonesian stock market, while the stock markets of other countries do not exhibit such integration. This study contributes to the existing literature on stock market integration. Research on the integration of the Indonesian stock market with those of leading global economies remains limited, making this study an important reference. The findings provide valuable insights for both Indonesian investors and those from leading economies in formulating strategies for international portfolio diversification.